Characteristics on distribution of chemical composition in groundwater along the Mekong and Bassac (Hậu) river, Vietnam - Sato, Hikaru; Shibasaki, Naoaki; Lap, Nguyen Van; Oanh, Ta Thi Kim; Lan, Nguyen Thi Mong (Vietnam Journal of Earth Sciences, 2019)
Along the Mekong River (MR), arsenic contamination in the groundwater has been recognized since the 2000s. Due to arsenic contamination in shallow aquifers, the drinking water has been prevented from being contaminated with arsenic by installing wells, 200 m to 400 m deep. However, it has been known that groundwater was contaminated by not only arsenic but also other trace elements. The need to reveal characteristics on the distribution of chemical composition by horizontally and vertically is increasing for purposes of appropriate development and management of groundwater. This study summarized the results of surveys for arsenic since 2008 and surveys for dissolved ions and trace elements since 2015, and described characteristics on distribution for chemical composition at the regional areas along the MR and Bassac (Hậu) River (BR). Groundwater samples were collected from existing wells in 8 provinces and 1 city. The authors used Piper and Stiff diagram that reflect the chemical composition of groundwater to respond to varying horizontal and vertical distributions. The Principal Component Analysis (PCA) was also carried out to reveal the correspondences of dissolved ions and trace elements. Variety concentrations and distributions of ions and trace elements show the obvious distinction between upper (<200 m deep) and lower (>200 m deep) aquifers broadly divided by geologic age. A wide variety of ion compositions and trace elements was found in the upper aquifer, and concentration of some trace elements in groundwater was high and exceed the World Health Organization (WHO) drinking water guideline value. On the other hand, groundwater in the lower aquifer is simple and rarely contaminated by trace elements. However, the arsenic concentration ranging from 0.01–0.065 mg/L slightly exceeding the WHO guideline value was found at the lower aquifer in the downstream areas of the Mekong River Delta. These results on the distribution analysis provide the insight that deep groundwater is not necessarily safe by over-pumping from deep aquifer and drilling new wells in the downstream areas.